Religion and Anticorruption Governance in Indonesia - Noer, Hamka Hendra (Universitas Islam Negeri Raden Intan Lampung, 2025)
This article examines the relationship between religiosity and corruption in post-Reform Indonesia, positioning religion as both a normative foundation and an ethical framework for governance. Historically, the principle of Belief in the One and Only God enshrined in Pancasila aimed to reinforce moral integrity within state administration. However, recent political developments indicate an increasing appropriation of religious values, undermining their effectiveness as genuine moral guides in political power. Through a qualitative literature review and cross-national comparative analysis, this study explores the connections among religious values, moral consciousness, and the quality of political institutions. The findings reveal that Islamic ethical principles such as ghulul (misappropriation of public resources), risywah(bribery), and khianat (betrayal of trust) strongly condemn abuses of power and violations of public trust; however, they are insufficient to combat corruption without robust institutional support. Comparative analysis with advanced democracies, including Germany, Japan, and Scandinavian countries, demonstrates that governance integrity is primarily maintained by the rule of law, a transparent political culture, and accountable institutions, rather than by high levels of societal religiosity. Conversely, in developing countries like Indonesia and Bangladesh, high religiosity often coexists with social tolerance toward corruption due to weak law enforcement and entrenched patronage-based political cultures. This study emphasizes the need for a dual strategy to combat corruption in Indonesia: internalizing religious moral values at the individual level while strengthening political institutions to enhance transparency, accountability, and support for substantive democracy. Practically, these findings highlight the importance of integrating religious ethical values into anticorruption policies, bureaucratic reforms, and the enhancement of law enforcement institutions to promote sustainable and integrity-based governance.